Design of Realtime Web Application Firewall on Deep Learning-Based to Improve Web Application Security - Rofif Zainul Muttaqin; Dodi Sudiana (Postgraduate, University of Mataram, 2024)
Web applications are widely used nowadays, but comprises several vulnerabilities that are often used by attacker to exploit the system. There is web application firewall (WAF) that could mitigate these problem. WAF generally works based on pre-established rules. However, the weakness of this system is the evolving nature of attacks, and configuring rules on WAF requires in-depth knowledge related to existing applications. Artificial intelligence technology, both machine learning (ML) and deep learning (DL), shows good potential in recognizing types of attacks. In this research, a Real-time DL-based WAF was built to enhance security in web applications. Various ML and DL models were tested to perform the task of web attack detection, including Support Vector Machine (SVM), Random Forest (RF), Convolutional Neural Network (CNN), and Long Short-Term Memory (LSTM). Based on the test results, the CNN-LSTM model achieved the highest performance, namely an accuracy of 98.61%, precision of 99%, recall of 98.08%, and f1-score of 98.54%. From the testing results with a web vulnerability scanner, the performance of the DL-based WAF is not inferior to ModSecurity WAF, which is used as a comparison. From the analysis results, it can be concluded that the implementation of DL-based WAF can improve the security of web applications.